Simonachorutes, a new genus of Pseudachorutinae (Collembola, Neanuridae) from Europe - Skarżyński, Dariusz; Arbea, Javier I.; Piwnik, Agata (Zootaxa, 2016)
Simonachorutes gen. nov. a new genus of subfamily Pseudachorutinae is described from Europe. It has a unique suite of morphological characters (8 + 8 ocelli, very long buccal cone, mandibles absent, tibiotarsal chaetotaxy reduced, furcula present) and is similar to Pseudachorutes Tullberg, 1871, Paranurida Skarżyński & Pomorski, 1994 and Pongeia Najt & Weiner, 2002. S. romeroi comb. nov. and S. agrensis comb. nov. are redescribed and S. weinerae sp. nov. from Poland is described.